Effect of botulinum toxin A on the intraocular pressure and the retina in an animal model. (June 2013) - Gatzioufas, Zisis; Stupp, Tobias; Moschos, Marilita M.; Kopsidas, Konstantinos; Charalambous, Petar; Thanos, Solon
<x xml:space="preserve">Abstract</x> Objective: The purpose of our study was to investigate the effect of an inadvertent intravitreal injection of botulinum toxin A (BTA) on the intraocular pressure (IOP) and the retina in an animal model. Methods: BTA was injected intravitreally in normotensive rats. IOP was measured preoperatively as well as 1, 2, and 4 weeks postoperatively. Retinas were stained in vivo using a retrograde labelling technique and the density of retinal ganglion cells (RGCs) was determined. Immunohistochemistry was performed for rhodopsin and retinal glial fibrillary acidic protein (GFAP). Results: Significant temporary IOP elevation occurred in all groups in the immediate postoperative period (ANOVA, p < 0.05). IOP changes in the intermediate period were not statistically significant (ANOVA, p > 0.05). The differences in the density of RGCs after BTA injection were not statistically significant (ANOVA, p > 0.05). All retinas displayed the same immunostaining pattern for rhodopsin and GFAP. Conclusion: Our findings indicate that BTA has probably no severe impact on IOP and the retina after an inadvertent intravitreal injection. However, temporary rise of IOP may possibly occur in the immediate postoperative period due to a volume-effect.